Management of anaemia and iron deficiency in patients with cancer: ESMO Clinical Practice Guidelines - Aapro, Matti S.; Jordan, Karin (Annals of oncology, 2018)
Anaemia and iron deficiency (ID) are frequent complications in patients with solid tumours or haematological malignancies, particularly in patients treated with
Gesehen am 02.04.2019
Published online 20 February 2018